Evaluation of Biological Treatments for the Adsorption of Phenol from Polluted Waters - A. Namane; O. Ali; H. Cabana; A. Hellal (Adsorption Science & Technology)
In this study, we describe the efficiency of three biological techniques (using Pseudomonas aeruginosa ) for the removal of phenol from polluted water. We explore the possibilities of elimination with free bacteria present in solution, fixed bacteria on granular activated carbon (GAC) and immobilized bacteria in calcium alginate beads. Our study results show that for all the three methods the removal of phenol from solution (300 mg l −1 ) is complete. The kinetic constants for phenol removal are equivalent for two methods, namely, bacteria fixed on the GAC and those immobilized in calcium alginate beads (≈0.2 h −1 ), while for the free bacteria in solution, it is about half of this value. We also report how the biomass production in solution depends on the method applied. The concentration seems to act as a regulator for the amount of bacteria released in solution.